Native Chicken from Chotanagpur Plateau: Morphological, Behavioral, Growth, and Reproductive Performance - KAMAL, REENA KUMARI; Poolangulam Chinnakkan Chandran, P C CHANDRAN; Amitava Dey; Rekha Sharma; A.K. Mishra; Rajni Kumari; Shanker Dayal; Rakesh Kumar; Manoj Tripathi; Anup Das (The Indian Journal of Animal Sciences, 2026)
The Native chicken population in Jharkhand surpasses the improved chicken population by nearly 24 times. Nonetheless, the region lacks formally recognized chicken breeds, despite the widespread success and traditional practices of raising lesser-known breeds. The present study was conducted to describe the phenotypic characteristics, production efficiency and certain behavioural characteristics of native Mala Chicken of Chotanagpur plateau of India. Field observations, farmer interviews, and controlled rearing under simulated field conditions, were used to collect data. A total of 736 adult chickens were sampled and characterized for 17 quantitative traits and 438 adult chickens for 10 qualitative traits. The   black & golden mix (38.88%) followed by white & black mix (37.80%) plumage colour in males and white & black (34.60%) followed by brownish white to light brown (31.18%) plumage colour in females were dominant in the ‘Mala’ chicken. The single comb was the most prevalent. In males, the hackle and saddle feathers displayed a rich golden-yellow hue, forming a garland-like pattern with laced plumage. Predominantly, the native chicken possesses white skin colour (73.28%), red earlobe (55.92%) and yellow shank (64.46%). The mean body weights of indigenous male and female chickens were found to be 1.86±0.04 kg and 1.09±0.02 kg, respectively. The average values for body length (cm), back length (cm), wingspan (cm), comb length (cm), shank length (cm) was 39.30±0.16, 27.22±0.13, 34.00±0.20, 5.76±0.18, 9.49±0.06 respectively. Average age at first egg, annual egg production, clutch length, number of clutches and average numbers of eggs laid per cycle of indigenous chickens obtained in the present study were 209.71±0.94 days, 68.94±0.98, 12.87±0.34, 2.41±0.08 days and 12.75±0.37 respectively. The flight distance and height were recorded as 40.14 ft and 8.35 ft, respectively, while the territory radius of cocks measured 122.69 ft. The findings of this study offer baseline data on the phenotypic, production, and behavioral traits of native chicken germplasm from the Chotanagpur Plateau, India. Further efforts should be directed toward their conservation and enhancement.